Optimizing the Ability to Handle Toxic and Hazardous Waste Through Problem-Based Learning - Azzajjad, Muhammad Fath; Ahmar, Dewi Satria; Ahmar, Ansari Saleh (PT ARRUS Intelektual Indonesia, 2023)
The purpose of this study is to compare the efficacy of the Problem-Based Learning (PBL) learning model to traditional learning in developing the competence to manage Hazardous and Toxic Materials (B3) in basic laboratory courses. In this form of experimental research utilizing a Pre-Test and Post-Test Control Group Design, The N-gain values in the experimental (0.774) and control (0.8163) groups increased significantly, with g> 0.7 indicating a high category. The N-gain percent in the experimental (77.4026) and control (81.627) courses topped 76%, showing that both learning approaches were effective. Even though the Mann-Whitney non-parametric test revealed no significant difference between the experimental and control groups on the posttest and pretest, the conclusion that PBL had no meaningful impact must be regarded in the context of this study. Overall, both PBL and traditional methods improved B3 handling abilities, and these findings may aid in the creation of more effective learning methodologies in the future.